The Impact of the Virality of the Presidential Diploma Issue in the Era of Information Disruption on the Governance of Indonesian State Administration - Barham Siregar (Universitas Medan Area, 2026)
The era of information disruption has brought significant changes to governance, particularly in terms of transparency, accountability, and public legitimacy. The virality of the presidential diploma issue in Indonesia serves as a concrete example of how a personal issue can escalate into a national debate, impacting public trust in the government. This study aims to describe the process of the presidential diploma issue's virality within the context of information disruption and analyze its impact on legitimacy and governance in Indonesia. The method used was a qualitative case study design. Data were obtained from academic literature, mass media coverage, social media content, and independent online media. Data collection techniques included documentation studies, digital discourse observations, and interviews. Data analysis employed a critical discourse analysis approach, emphasizing how narratives are produced, distributed, and received in the digital public sphere. The results show that the issue's virality is shaped through the interaction between social media algorithms, online media framing, and the involvement of political actors. This issue has resulted in declining public trust and weakening government legitimacy, despite formal clarification. The government's response has been deemed slow, reactive, and has not fully utilized regulations on information disclosure or the public document digitization system.